Spatio-Temporal Distribution of Brachyuran Zoea in Vembanad lake, South India: Influence of Salinity Zones and Seasonal Variations - Sruthi, K.,; Nidhin, B.,; Mahadevan, Harikrishnan (Fishery Technology, 2025)
This study investigates the spatio-temporal distribution of brachyuran larvae in Vembanad Lake, a tropical estuarine ecosystem. The research categorizes the estuary into three salinity zones: polyhaline, mesohaline, and oligohaline. It analyzes larval abundance in relation to key environmental factors, including temperature, salinity, pH, and dissolved oxygen. Data collected across multiple seasons showed that larval abundance peaked during the pre-monsoon season and significantly declined during the monsoon season. The mesohaline zone exhibited the highest larval abundance, indicating that it was a crucial habitat for brachyuran larval development. The findings emphasized the impactof seasonal freshwater influx during the monsoon, which transformed the estuary into a freshwater system, posing significant challenges for marine larvae. These results contributed to the understanding of larval distribution in tropical estuaries and have implications for the conservation and management of these critical habitats.